Novel c‐di‐GMP recognition modes of the mouse innate immune adaptor protein STING. Corrigendum. (21st May 2013) - Chin, Ko‐Hsin; Tu, Zhi‐Le; Su, Yi‐Che; Yu, Yu‐Jen; Chen, Hui‐Chen; Lo, Yuan‐Chao; Chen, Chin‐Pan; Barber, Glen N.; Chuah, Mary Lay‐Cheng; Liang, Zhao‐Xun; Chou, Shan‐Ho
<x xml:space="preserve">Abstract</x> The two structures reported in the article by Chin et al. [(2013). Acta Cryst. D69, 352–366] have been further refined and corrected.